Gas-liquid flows in inclined pipes and venturis - Geraci, Giorgio (2006)
In oil industrial applications, the modem practice in the drilling of oil wells, deviated drilling, results in inclinations from the vertical to the horizontal being present in such wells. Their design requires an accurate knowledge of the pressure drop/flowrates/physical-properties relationships. The measurement of wet-gas streams can be improved significantly by the use of a Venturi flow meter with an "overreading" correction. Moreover, at high gas mass fractions, knowledge of the liquid distribution about the well tubing cross section is required to inform policy on the use of inhibitors to protect the tubing from corrosion.